2013
DOI: 10.3109/21691401.2012.751180
|View full text |Cite
|
Sign up to set email alerts
|

Novel Nanodimension artificial red blood cells that act as O2and CO2carrier with enhanced antioxidant activity: PLA-PEG nanoencapsulated PolySFHb-superoxide dismutase-catalase-carbonic anhydrase

Abstract: Poly(ethylene glycol)-Poly(lactic acid) block-copolymer (PEG-PLA) was prepared and characterized using Fourier transform infrared spectrophotometer (FTIR). Glutaraldehyde was used to crosslink stroma-free hemoglobin (SFHb), superoxide dismutase (SOD), catalase (CAT), and carbonic anhydrase (CA) into a soluble complex of PolySFHb-SOD-CAT-CA. PEG-PLA was then used to nanoencapsulated PolySFHb-SOD-CAT-CA by oil in water emulsification. This resulted in the formation of PLA-PEG-PolySFHb-SOD-CAT-CA nanocapsules tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Similarly, an increase in enzyme liposomal entrapment efficiency occurred with increasing the initial enzyme concentration up to a certain limit followed by a decrease in EE [17,34]. It was previously reported that catalase activity was stabilized upon incorporation into vesicles [35], similarly catalase antioxidant activity was enhanced upon nano-encapsulation [36,37].…”
Section: Optimization Of Encapsulation Conditionsmentioning
confidence: 91%
“…Similarly, an increase in enzyme liposomal entrapment efficiency occurred with increasing the initial enzyme concentration up to a certain limit followed by a decrease in EE [17,34]. It was previously reported that catalase activity was stabilized upon incorporation into vesicles [35], similarly catalase antioxidant activity was enhanced upon nano-encapsulation [36,37].…”
Section: Optimization Of Encapsulation Conditionsmentioning
confidence: 91%
“…Further, the laccase enzyme was immobilized along with stabilizing and cross-linking agents such as BSA and glutaraldehyde and packed in Teflon tube to fabricate amperometric biosensors. Bifunctional agents such as glutaraldehyde cross-link with the reactive amino groups of enzymes (Gao et al 2013). The incorporation of BSA along with glutaraldehyde during the process of enzyme immobilization through hydrophobic interactions, contributed to the longterm operational stability of the enzyme biosensor.…”
Section: Resultsmentioning
confidence: 99%
“…This result is different from previous study of other PLA-PEG-based HbPN system. It has been reported that (Gao et al 2013), after encapsulating the soluble complex of PolySFHb-SOD-CAT-CA, the PLA-PEG NPs become homogeneous particles with core-shell structure. This phenomenon is mainly due to the absence of the surfactant residue on the surface of the HbPNs.…”
Section: Physicochemistry Characteristics Of the Hbpnmentioning
confidence: 99%